Nomenclatural reconsideration of the genera Aeschnophlebia Selys, 1883 and Planaeschna McLachlan, 1896 (Odonata, Aeshnidae) - Kosterin, Oleg E. (Zootaxa, 2023)
The nominal species Aeschna milnei Selys, 1883 and Aeschnophlebia optata Selys, 1883 are considered subjective synonyms, with A. milnei as the valid name based on an act of the First Reviser. Since A. milnei is the type species of Planaeschna McLachlan, 1896, and A. optata is the type species of Aeschnophlebia Selys, 1883 (by subsequent designation), both nominal genera are also subjective synonyms, with Aeschnophlebia as the valid name. Species until recently included in Aeschnophlebia (except the type species), are now considered congeneric with Aeshna vernalis Vander Linden, 1820, the type species of Brachytron Evans, 1845 and a junior subjective synonym of B. pratense (Müller, 1764). The present paper provides the correct combinations and name spellings for all subspecies presently assigned to the genera Planaeschna and Aeschnophlebia.